Effect of Supplementation Different Levels of Cheese Whey to Dietary Treated Baggase on In-Vitro Nutrients Digestibility, Rumen Environment and Gas Production - A. Atta Elmnan, Balgees; Abkar, Huda, M. A. (Journal of Veterinary Medicine and Animal Production, 2021)
The study aimed to assess the effect of supplementing cheese whey at levels of 0% (T0%), 5% (T5%), 10% (T10%), 15% (T15%) and 20% (T20%) to dietary urea treated baggase on in-vitro digestibility of dry matter (IVDMD), organic matter (IVOMD), crud protein (IVCPD), neutral detergent fiber (IVNDFD), rumen environment and gas production. The results indicated that the cheese whey supplementation to the dietary urea treated baggase significantly (P<0.05) had positive effect on IVDMD, IVOMD, IVCPD and IVNDFD with superior effect for T5%. The pH was significantly (P<0.05) decreased for supplementing diets and stable at the following values: 6.25, 6.32, 6.39 and 6.54 for T0%, T5%, T10%, T15% and T20% respectively. The same trend was recorded for ammonianitrogen concentration (5mg/100dl) and the concentration of all diets was above the recommended level (5mg/100dl). Volatile fatty acids concentration (mmol/100ml) was significantly (P<0.05) increased in whey diets (27.57, 33.2, 32.87, 32.52 and 31.85 for T5%, T10%, T15% and T20% respectively) and decreased in control diet (27.57). The highest values of gas production and its fermentable fractions were gained by T5% diet. In conclusion supplementation of dietary urea treated baggase with different level of cheese whey had positive effects on nutrients digestibility, volatile fatty acids and gas production and its fractions with superior effect for T5% diet